Biomechanical evaluation of a novel barbed suture pattern with epitendinous suture augmentation in a canine flexor tendon model. Issue 5 (7th May 2021) - Duffy, Daniel J.; Chang, Yi‐Jen; Fisher, Matthew B.; Moore, George E.
Abstract: Objective: To determine the effect of a novel barbed suture pattern (NBSP) compared to a three‐loop‐pulley (3LP) with and without epitendinous suture (ES) augmentation on the biomechanical strength and gap formation of repaired canine tendons. Study Design: Ex vivo, cadaveric, randomized, experimental study. Sample Population: Forty, adult superficial digital flexor tendons (SDFT). Methods: SDFT were randomly assigned to one of four groups ( n = 10/group). Sharp tenotomy was performed and repaired with 3LP, NBSP, 3LP + ES, and NBSP + ES. Constructs were tested to failure while evaluating yield, peak, and failure loads, loads at 1 and 3 mm gap formation, and failure mode. Results: Constructs augmented with ES sustained 80% greater yield ( p < .001), peak ( p < .001), and failure ( p < .001) loads, with no difference between 3LP + ES and NBSP + ES constructs regarding peak ( p = .614), and failure forces ( p = .865). Loads resulting in 1 and 3 mm gap formation were greater when constructs were augmented with an ES ( p ≤ .003). Failure mode differed between groups ( p < .001), occurring predominantly due to suture pull‐through in 3LP and NBSP groups compared to tissue failure distant to the repair site in ES augmented constructs. Conclusion: Tendons repaired with the NBSP used in this study resisted similar forces as those repaired with 3LP. Augmentation with an ES improved the biomechanical properties of repaired constructs, including resistance to gap formation. Clinical Relevance: The NBSP repair tested here may be advantageous over monofilament suture repair as it uses a similar‐sized barbed core suture but eliminates the requirement for knot tying.